If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(8x + -2) = -8x + -3 Reorder the terms: 10 + -1(-2 + 8x) = -8x + -3 10 + (-2 * -1 + 8x * -1) = -8x + -3 10 + (2 + -8x) = -8x + -3 Combine like terms: 10 + 2 = 12 12 + -8x = -8x + -3 Reorder the terms: 12 + -8x = -3 + -8x Add '8x' to each side of the equation. 12 + -8x + 8x = -3 + -8x + 8x Combine like terms: -8x + 8x = 0 12 + 0 = -3 + -8x + 8x 12 = -3 + -8x + 8x Combine like terms: -8x + 8x = 0 12 = -3 + 0 12 = -3 Solving 12 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (3x^9)(2x^3)= | | -2x+6=4x | | 37-x+9x-27=180 | | 3(5c+3)-28=11c+1 | | -x-4=-15 | | (3x^8)(-6)= | | 5x+6=126 | | 3a-3=-11 | | 3-2x=12+7x | | 4a(3a-5b)= | | 5x^2+29-6= | | 5x-y=24 | | -6/7x+15=-33 | | 26x+21=32x-9 | | 3x^2+10x=32 | | 1/9y=-7 | | -4(y-9)=-10(2-y) | | x=4x+2 | | z-1/2=-1/4 | | .3x-4.2=2.4 | | .3-4.2=2.4 | | 60-2x=30 | | 12/18 | | 6-66.6666666667x=-8 | | 19+0+(-9)= | | 6/18+3/19 | | 8/11-4/15 | | 4/9+m=20 | | y=-5x^2+30t+2 | | 2*3*4*5= | | 3x-23=1-4x | | 4/16+2/13 |